Interweaving identity and digital fandom social movements: A case study of the “BTS Army Indonesia Peduli Bencana” - Vina Nahdiyah Wahyuningtyas; Ade Kusuma (SIMULACRA: JURNAL SOSIOLOGI, 2021)
Digital fandom appears as a part of the development of popular culture in today’s digital era. One of the interesting digital fandom activities to be studied is a series of campaign activities, fundraising, and charity projects of the ”ARMY Indonesia Peduli Bencana” by BTS Army Indonesia. This study used qualitative descriptive research and observation, interviews, documentation, and literature study data collection method. Researchers interviewed BTS Army Indonesia fanbase admins and Instagram account followers of @btsarmyina.project involved in the ”ARMY Indonesia Peduli Bencana” project. This study showed that fans reflect the idol and the cultural identity of fan groups in today’s digital era can be seen from digital fandom activities in online media. Fanbase and influencers have the power in moving their followers to be actively involved in social activities carried out on online media: they act as social agents who actively campaign a humanity project as a cultural identity of a fandom adopted from the idol groups’ values. In addition, the convenience of technology is one of the considerations for fans in participating as volunteers and donors in these humanitarian activities. The success of fundraising, charity and the ”ARMY Indonesia Peduli Bencana” campaign manifests online social movement conducted by fandom in the digital era.